Frontières physiques et frontières ethniques au Kurdistan irakien : le cas particulier des Yézidis du Sinjar - Paul Calvaillé (Les Cahiers d’EMAM)
The Kurdistan Democratic Party, in its opposition to the central Iraqi state, has been implementing various strategies since 2003 to claim and control parts of the “disputed territories”. Among these strategies, the party has pursued a significant ethno-political entrepreneurship policy targeting Kurdish or Kurdish-speaking populations in these territories. One of these areas is the Sinjar district, primarily inhabited by the Kurdish-speaking Yezidi religious minority. Despite the substantial efforts invested in this initiative between 2003 and 2014, the majority of Yezidis in Sinjar today reject the Kurdish identity and, consequently, the KDP’s intention to incorporate Sinjar into Iraqi Kurdistan. This situation is primarily explained by the discrimination faced by Yezidis in the predominantly Muslim Kurdish society of the Kurdistan Regional Government (KRG), but especially by the abandonment of Sinjar by Kurdish military forces during the offensive by the Islamic State organization (Daesh) in August 2014.